PATTERNS OF CIRCULATING FSH AND LH IN OULED DJELLEL EWE LAMBS DURING POSTNATAL DEVELOPMENT (Sciences & Technologie. C, Biotechnologies, 2011)
Plasma  was collected for hormone measurement  from 150 Ouled Djellel ewe lambs, born in September, at 0 (